Air Pollution as an Important Factor in Construction Materials Deterioration in Slovak Republic. (2015) - Ivaskova, Martina; Kotes, Peter; Brodnan, Miroslav
Abstract: Climatic parameters and atmospheric pollution are highly relevant to the degradation of several building materials like construction metallic materials, concrete structures and plasters of buildings, bridges or art sculptures. Degradation of not only metal materials, but also other construction materials (concrete, glass, etc.) by chemical environmental loads is an increasingly serious problem not only in Slovakia, but all over the world. The atmosphere and, ultimately, the hydrosphere could be particularly polluted by industrial activity, thus causing an increased corrosion aggressiveness of atmosphere. In the article, the air pollution impact on stone materials and carbon steel in Slovak Republic is observed. In the evaluation, there are used dose-response functions, which were developed based on long-term research by the other authors. Effectively, multi-annual climatic parameters and parameters of air pollution in Slovak Republic were used for generation of the maps of annual average surface loss of stone materials and carbon steel. One of the priorities of that research is creation of corrosion maps of different materials, which do not help to protect materials, but could be useful for prediction of risks during design, analysis and maintenance. The values obtained from this interpolation of the maps would be used as a basis for a long-term research work in mapping the state of degradation of various materials in Slovak Republic.